Absorptive Capacity in Supply Chains: Does Responsive Strategy of a Firm Matter? - Sriparinya Toopgajank; Piyada Wongwiwat (International Journal of Supply Chain Management, 2019)
The main purpose of the current study is to investigate the impact of absorptive capacity on supply chains. In addition to that, the study has examined the mediating role of responsive strategy in the relationship between absorptive capacity in supply chain and performance. This research is based on the analysis of absorptive capacity to be an organizational value making a firm able to gather, use, and implement the information from outside. The study demonstrates the association between absorptive capacity and responsive strategy. It has been analyzed the way in which absorptive capacity has been developed by firms through examination of curvilinear impact of responsive strategy. the study is among the pioneering studies on the issues. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the current study have provided support to with the hypothesized results. This study will be helpful for policymakers and researchers in examining the link absorptive capacity on supply chains, responsive strategy and performance.